qanda-logo
search-icon
Symbol
apple-logo
google-play-logo

Calculator search results

Formula
Solve the quadratic equation
Answer
circle-check-icon
expand-arrow-icon
expand-arrow-icon
expand-arrow-icon
expand-arrow-icon
Number of solution
Answer
circle-check-icon
expand-arrow-icon
Relationship between roots and coefficients
Answer
circle-check-icon
Graph
$y = x ^ { 2 } - 5 x - 2$
$y = 0$
$x$Intercept
$\left ( \dfrac { 5 } { 2 } + \dfrac { \sqrt{ 33 } } { 2 } , 0 \right )$, $\left ( \dfrac { 5 } { 2 } - \dfrac { \sqrt{ 33 } } { 2 } , 0 \right )$
$y$Intercept
$\left ( 0 , - 2 \right )$
Minimum
$\left ( \dfrac { 5 } { 2 } , - \dfrac { 33 } { 4 } \right )$
Standard form
$y = \left ( x - \dfrac { 5 } { 2 } \right ) ^ { 2 } - \dfrac { 33 } { 4 }$
$x ^{ 2 } -5x-2 = 0$
$\begin{array} {l} x = \dfrac { 5 + \sqrt{ 33 } } { 2 } \\ x = \dfrac { 5 - \sqrt{ 33 } } { 2 } \end{array}$
Solve quadratic equations using the square root
$\color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 5 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 2 } = \color{#FF6800}{ 0 }$
$ $ Convert the quadratic expression on the left side to a perfect square format $ $
$\left ( \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 5 } { 2 } } \right ) ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 2 } \color{#FF6800}{ - } \left ( \color{#FF6800}{ \dfrac { 5 } { 2 } } \right ) ^ { \color{#FF6800}{ 2 } } = \color{#FF6800}{ 0 }$
$\left ( x - \dfrac { 5 } { 2 } \right ) ^ { 2 } \color{#FF6800}{ - } \color{#FF6800}{ 2 } \color{#FF6800}{ - } \left ( \color{#FF6800}{ \dfrac { 5 } { 2 } } \right ) ^ { \color{#FF6800}{ 2 } } = 0$
$ $ Move the constant to the right side and change the sign $ $
$\left ( x - \dfrac { 5 } { 2 } \right ) ^ { 2 } = \color{#FF6800}{ 2 } \color{#FF6800}{ + } \left ( \color{#FF6800}{ \dfrac { 5 } { 2 } } \right ) ^ { \color{#FF6800}{ 2 } }$
$\left ( x - \dfrac { 5 } { 2 } \right ) ^ { 2 } = 2 + \left ( \color{#FF6800}{ \dfrac { 5 } { 2 } } \right ) ^ { \color{#FF6800}{ 2 } }$
$ $ When raising a fraction to the power, raise the numerator and denominator each to the power $ $
$\left ( x - \dfrac { 5 } { 2 } \right ) ^ { 2 } = 2 + \dfrac { \color{#FF6800}{ 5 } ^ { \color{#FF6800}{ 2 } } } { \color{#FF6800}{ 2 } ^ { \color{#FF6800}{ 2 } } }$
$\left ( \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 5 } { 2 } } \right ) ^ { \color{#FF6800}{ 2 } } = \color{#FF6800}{ 2 } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 5 ^ { 2 } } { 2 ^ { 2 } } }$
$ $ Organize the expression $ $
$\left ( \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 5 } { 2 } } \right ) ^ { \color{#FF6800}{ 2 } } = \color{#FF6800}{ \dfrac { 33 } { 4 } }$
$\left ( \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 5 } { 2 } } \right ) ^ { \color{#FF6800}{ 2 } } = \color{#FF6800}{ \dfrac { 33 } { 4 } }$
$ $ Solve quadratic equations using the square root $ $
$\color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 5 } { 2 } } = \pm \sqrt{ \color{#FF6800}{ \dfrac { 33 } { 4 } } }$
$\color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 5 } { 2 } } = \pm \sqrt{ \color{#FF6800}{ \dfrac { 33 } { 4 } } }$
$ $ Solve a solution to $ x$
$\color{#FF6800}{ x } = \pm \color{#FF6800}{ \dfrac { \sqrt{ 33 } } { 2 } } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 5 } { 2 } }$
$\color{#FF6800}{ x } = \pm \color{#FF6800}{ \dfrac { \sqrt{ 33 } } { 2 } } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 5 } { 2 } }$
$ $ Separate the answer $ $
$\begin{array} {l} \color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 5 } { 2 } } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { \sqrt{ 33 } } { 2 } } \\ \color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 5 } { 2 } } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { \sqrt{ 33 } } { 2 } } \end{array}$
$\begin{array} {l} \color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 5 } { 2 } } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { \sqrt{ 33 } } { 2 } } \\ \color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 5 } { 2 } } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { \sqrt{ 33 } } { 2 } } \end{array}$
$ $ Organize the expression $ $
$\begin{array} {l} \color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 5 + \sqrt{ 33 } } { 2 } } \\ \color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 5 - \sqrt{ 33 } } { 2 } } \end{array}$
$\begin{array} {l} x = \dfrac { 5 + \sqrt{ 33 } } { 2 } \\ x = \dfrac { 5 - \sqrt{ 33 } } { 2 } \end{array}$
Calculate using the quadratic formula
$x = \dfrac { \color{#FF6800}{ - } \left ( \color{#FF6800}{ - } 5 \right ) \pm \sqrt{ \left ( - 5 \right ) ^ { 2 } - 4 \times 1 \times \left ( - 2 \right ) } } { 2 \times 1 }$
$ $ Simplify Minus $ $
$x = \dfrac { 5 \pm \sqrt{ \left ( - 5 \right ) ^ { 2 } - 4 \times 1 \times \left ( - 2 \right ) } } { 2 \times 1 }$
$x = \dfrac { 5 \pm \sqrt{ \left ( \color{#FF6800}{ - } \color{#FF6800}{ 5 } \right ) ^ { \color{#FF6800}{ 2 } } - 4 \times 1 \times \left ( - 2 \right ) } } { 2 \times 1 }$
$ $ Remove negative signs because negative numbers raised to even powers are positive $ $
$x = \dfrac { 5 \pm \sqrt{ 5 ^ { 2 } - 4 \times 1 \times \left ( - 2 \right ) } } { 2 \times 1 }$
$x = \dfrac { 5 \pm \sqrt{ \color{#FF6800}{ 5 } ^ { \color{#FF6800}{ 2 } } - 4 \times 1 \times \left ( - 2 \right ) } } { 2 \times 1 }$
$ $ Calculate power $ $
$x = \dfrac { 5 \pm \sqrt{ \color{#FF6800}{ 25 } - 4 \times 1 \times \left ( - 2 \right ) } } { 2 \times 1 }$
$x = \dfrac { 5 \pm \sqrt{ 25 - 4 \color{#FF6800}{ \times } \color{#FF6800}{ 1 } \times \left ( - 2 \right ) } } { 2 \times 1 }$
$ $ Multiplying any number by 1 does not change the value $ $
$x = \dfrac { 5 \pm \sqrt{ 25 - 4 \times \left ( - 2 \right ) } } { 2 \times 1 }$
$x = \dfrac { 5 \pm \sqrt{ 25 \color{#FF6800}{ - } \color{#FF6800}{ 4 } \color{#FF6800}{ \times } \left ( \color{#FF6800}{ - } \color{#FF6800}{ 2 } \right ) } } { 2 \times 1 }$
$ $ Multiply $ - 4 $ and $ - 2$
$x = \dfrac { 5 \pm \sqrt{ 25 + \color{#FF6800}{ 8 } } } { 2 \times 1 }$
$x = \dfrac { 5 \pm \sqrt{ \color{#FF6800}{ 25 } \color{#FF6800}{ + } \color{#FF6800}{ 8 } } } { 2 \times 1 }$
$ $ Add $ 25 $ and $ 8$
$x = \dfrac { 5 \pm \sqrt{ \color{#FF6800}{ 33 } } } { 2 \times 1 }$
$x = \dfrac { 5 \pm \sqrt{ 33 } } { 2 \color{#FF6800}{ \times } \color{#FF6800}{ 1 } }$
$ $ Multiplying any number by 1 does not change the value $ $
$x = \dfrac { 5 \pm \sqrt{ 33 } } { \color{#FF6800}{ 2 } }$
$\color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 5 \pm \sqrt{ 33 } } { 2 } }$
$ $ Separate the answer $ $
$\begin{array} {l} \color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 5 + \sqrt{ 33 } } { 2 } } \\ \color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { 5 - \sqrt{ 33 } } { 2 } } \end{array}$
$ $ 2 real roots $ $
Find the number of solutions
$\color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 5 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 2 } = \color{#FF6800}{ 0 }$
$ $ Determine the number of roots using discriminant, $ D=b^{2}-4ac $ from quadratic equation, $ ax^{2}+bx+c=0$
$\color{#FF6800}{ D } = \left ( \color{#FF6800}{ - } \color{#FF6800}{ 5 } \right ) ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 4 } \color{#FF6800}{ \times } \color{#FF6800}{ 1 } \color{#FF6800}{ \times } \left ( \color{#FF6800}{ - } \color{#FF6800}{ 2 } \right )$
$D = \left ( \color{#FF6800}{ - } \color{#FF6800}{ 5 } \right ) ^ { \color{#FF6800}{ 2 } } - 4 \times 1 \times \left ( - 2 \right )$
$ $ Remove negative signs because negative numbers raised to even powers are positive $ $
$D = 5 ^ { 2 } - 4 \times 1 \times \left ( - 2 \right )$
$D = \color{#FF6800}{ 5 } ^ { \color{#FF6800}{ 2 } } - 4 \times 1 \times \left ( - 2 \right )$
$ $ Calculate power $ $
$D = \color{#FF6800}{ 25 } - 4 \times 1 \times \left ( - 2 \right )$
$D = 25 - 4 \color{#FF6800}{ \times } \color{#FF6800}{ 1 } \times \left ( - 2 \right )$
$ $ Multiplying any number by 1 does not change the value $ $
$D = 25 - 4 \times \left ( - 2 \right )$
$D = 25 \color{#FF6800}{ - } \color{#FF6800}{ 4 } \color{#FF6800}{ \times } \left ( \color{#FF6800}{ - } \color{#FF6800}{ 2 } \right )$
$ $ Multiply $ - 4 $ and $ - 2$
$D = 25 + \color{#FF6800}{ 8 }$
$D = \color{#FF6800}{ 25 } \color{#FF6800}{ + } \color{#FF6800}{ 8 }$
$ $ Add $ 25 $ and $ 8$
$D = \color{#FF6800}{ 33 }$
$\color{#FF6800}{ D } = \color{#FF6800}{ 33 }$
$ $ Since $ D>0 $ , the number of real root of the following quadratic equation is 2 $ $
$ $ 2 real roots $ $
$\alpha + \beta = 5 , \alpha \beta = - 2$
Find the sum and product of the two roots of the quadratic equation
$\color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 5 } \color{#FF6800}{ x } \color{#FF6800}{ - } \color{#FF6800}{ 2 } = \color{#FF6800}{ 0 }$
$ $ In the quadratic equation $ ax^{2}+bx+c=0 $ , if the two roots are $ \alpha, \beta $ , then it is $ \alpha + \beta =-\dfrac{b}{a} $ , $ \alpha\times\beta=\dfrac{c}{a}$
$\color{#FF6800}{ \alpha } \color{#FF6800}{ + } \color{#FF6800}{ \beta } = \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { - 5 } { 1 } } , \color{#FF6800}{ \alpha } \color{#FF6800}{ \beta } = \color{#FF6800}{ \dfrac { - 2 } { 1 } }$
$\alpha + \beta = \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { - 5 } { 1 } } , \alpha \beta = \dfrac { - 2 } { 1 }$
$ $ Solve the sign of a fraction with a negative sign $ $
$\alpha + \beta = \color{#FF6800}{ \dfrac { 5 } { 1 } } , \alpha \beta = \dfrac { - 2 } { 1 }$
$\alpha + \beta = \dfrac { 5 } { \color{#FF6800}{ 1 } } , \alpha \beta = \dfrac { - 2 } { 1 }$
$ $ If the denominator is 1, the denominator can be removed $ $
$\alpha + \beta = \color{#FF6800}{ 5 } , \alpha \beta = \dfrac { - 2 } { 1 }$
$\alpha + \beta = 5 , \alpha \beta = \dfrac { - 2 } { \color{#FF6800}{ 1 } }$
$ $ If the denominator is 1, the denominator can be removed $ $
$\alpha + \beta = 5 , \alpha \beta = \color{#FF6800}{ - } \color{#FF6800}{ 2 }$
Have you found the solution you wanted?
Try again
Try more features at Qanda!
Search by problem image
Ask 1:1 question to TOP class teachers
AI recommend problems and video lecture
apple-logo
google-play-logo